(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
Electrical capacitance tomography system is useful for obtaining information about the spatial distribution of a mixture of dielectric materials inside a vessel. This research aims to obtain real-time monitoring on the composition for liquid mixture in conveying pipeline. ECT is a non-invasive, non-intrusive and non-destructive technique that can measure the flow level inside a pipeline. In order to increase the image resolution and accuracy of current tomography research, a study on 16 electrodes sensor ECT system has been developed. The developed system has the flexibility to be assembled and moved from a pipeline to another. The intelligent on-board flexibility and mobility sensor technique is a new technique for ECT system. The system can be assembled in different diameter sizes of pipeline, and numbers of electrodes sensor can be reduced accordingly depending on the pipeline sizes without the need to redesign the electrodes sensor. The new design is equipped with high speed data processing rate data acquisition system and high speed data reconstruction. A microcontroller that support full-speed USB data transfer rate has been designed as the centralization control unit. In order to improve data result, iterative algorithm has been implemented in this system in order to obtain a precise image of the flow in the pipeline. As a result, the ECT system is able to reconstruct various multiphase flow images.Â